Cardiovascular screening for elite junior tennis players: the experience of the French Tennis Federation - Cousteau, J. P.; Montalvan, B.; Joumet, M.; Gires, A. (2001)
Cardiovascular screening recommendations have been introduced in France for health fitness facilities, master athletes, high school athletes at risk of sudden death and competitive athletes. Since 2000, cardiovascular screening has been compulsory for all elite athletes, as a preventive measure against the risk of sudden cardiac death. A list is drawn up by each sports federation and endorsed by the Ministry of Sports. Screening includes a clinical examination, an electrocardiogram (EKG), an exercise test (VO2 max) and an echocardiogram (ECG). Here we present screening results for male and female players aged 16 to 19, who train at the National Roland Garros Training Centre in Paris.